Толковый словарь русского языка: 80 000 слов и фразеологических выражений / С. И. Ожегов, Н. Ю. Шведова - Ожегов Сергей Иванович (ТЕХНОЛОГИИ, 2003)
Экземпляры: К/х (20020619) / Инвентарный номер: 49287 / Цена: 50.00 / Авт.знак: О-45 / ББК: 81.2Р-4